Nonlinear soil and pile behaviour on kinematic bending response of flexible piles. Issue 107 (April 2018) - Mucciacciaro, Michele; Sica, Stefania
Abstract: In recent years kinematic interaction of piled foundations under seismic loading has been extensively researched from both an experimental and a numerical viewpoint. With regard to numerical aspects, most literature studies implement simplified constitutive models to describe soil and pile behaviour despite current availability of sophisticated constitutive models for both materials. The use of advanced constitutive models is limited in practice due to the difficulty in calibrating several constitutive parameters and the high computation demand which is generally required, particularly if a 3D continuum approach is selected for the analysis. To overcome some of the difficulties above and achieve a better understanding on kinematic response of piles under strong earthquakes, the capability of an advanced but still user-friendly kinematic hardening constitutive soil model has been investigated. The model derives from the classical Von Mises failure criterion with the addition of isotropic and kinematic hardening components to better represent soil response under cyclic loading. Dynamic 3D finite element (f.e.) analyses were performed in the time domain through a simple scheme of a single pile embedded in a soil deposit made of two cohesive layers. The parametric study elucidates the role of soil nonlinearity (stiffness degradation, hysteresis, soil plasticization) on pile kinematic bending response in respect of the adopted input signal, mobilized transient and permanent shear strain developed in the soil layers. For some accelerometric inputs the diffuse plasticization of the soil around the pile leads to compute high kinematic bending moments especially in soil deposits with the upper layer made of low-plasticity index soft clay. Finally, pile nonlinearity has also been considered by implementing bending moment-pile curvature relationships typical of reinforced-concrete piles. Highlights: Kinematic pile bending is explored accounting for soil and pile nonlinearity. Soil nonlinearity is modelled by an advanced kinematic hardening constitutive law. Comparisons with previous literature data are presented. Soil nonlinearity affects more ground motion than pile-soil interplay. Pile yielding and failure may be achieved in layered subsoil.